Students' perception and satisfaction with use of electronic library services in academic libraries in Oyo state, Nigeria (2018)
The use of Information and Communication Technologies (ICTs) in library Services has a great potential to change the perception of users about Service Provision. It could also raise the expectation for the Provision of electronic cum digital library Services. Library users, sometimes, leave the library in frustration because they are hardly satisfied with the available Services in libraries. This study, therefore, investigates undergraduate students’ perception and satisfaction with electronic Services in selected academic libraries in Oyo State. The study adopted a survey research design with a study population of 10,018 registered users in four academic libraries. A sample size of 501 respondents was selected using stratified random sampling technique. A questionnaire titled “User Perception and Satisfaction with Electronic Library Services (UPSELS)” was used for data collection. The study revealed that electronic information resources, electronic databases, Internet access and Computer facilities are available in the surveyed academic libraries. Most students perceived that academic libraries need to introduce more electronic resources in their various disciplines. Few of the students were satisfied with available electronic information resources. The study observed problems such as poor network/Internet Connectivity, and poor awareness of students about electronic library Services. However, the advent of electronic Services has really geared students to crave for new Services that better address their growing yearning for satisfying information needs. Therefore, it is recommended that new electronic Services such as digital libraries, institutional repositories, and self-help Services should be introduced in line with best practices in the developed part of the world as this will increase the satisfaction level of users, especially, the undergraduate students.